The first record of Cyprinus rubrofuscus (Lacepède, 1803)In The Lower Part Of Al-asaad Lake Reservoir (Raqqa, Syria) - مجاهد بطل, محمد; منصور, كاترين; ديب, ديم (Latakia University Journal -Biological Sciences Series, 2021)
Common carp Cyprinus carpio fish spread in fresh water basins in Syria, especially in the Euphrates river, and the existence of Cyprinus rubrofuscus was not known in those basins. This research confirmed the first record of C. rubrofuscus in the lower part of Al-Asaad lake reservoir. 20 individuals of this specie were collected from Tabqa area during 2019/2020.The samples were transferred to the laboratory after being preserved in formaldehyde and were classified according to the international taxonomic keys. Also, morphometric characteristics were recorded in the laboratory. This specie was probably entered accidentally into the lake through the geographical continuity of the Euphrates river in Syria with both Iraq and Turkey.